A New Model to Calculate Stress Relaxation of Viscoelastic Material for Polyester-Wool-Spandex Yarn with Analytical Mechanics Approach - Valentinus Galih Vidia Putra; Juliany Ningsih Mohamad; Yusril Yusuf (Universitas Negeri Surabaya, 2021)
Many researchers have studied the mechanical properties of yarn in textile science because mechanical properties are the essential parameter in determining yarn quality. This research aims to make a new model and prediction of the material properties of textile yarns, especially for stress relaxation of viscoelastic textile yarn for polyester-wool-spandex yarn cases. In this research, a new approximation of the analytical mechanics model of stress relaxation using a system of four springs and a dashpot to determine viscoelastic yarn properties as polyester-wool-spandex has been studied. A yarn movement equation for viscoelastic yarn as polyester-wool-spandex having 36 yarn count number (in unit tex or g/km) has been formulated using analytical mechanics, and the model has been validated experimentally. The coefficient of determination R2 ranges from 0.82, which shows the closeness between the experimental results and the theoretical predictions. In this research, it is found that this model can be implemented to determine the viscoelastic material of yarn based on the properties of yarn as stress relaxation using the analytical mechanics approach.